2000
DOI: 10.7773/cm.v26i1.572
|View full text |Cite
|
Sign up to set email alerts
|

Advances in marine ecotoxicology: laboratory tests versus field assessment data on sediment quality studies

Abstract: Ecotoxicology is concerned with describing and predicting the behaviour of substances in the environment and the response of biological systems, and ultimately with assessing the risks associated with emissions. These assessments are complicated from a basic-science point of view and they should be carried out by using integrative assessments. Contaminated sediments are a significant regulatory issue with important science implications. Determining the impact of contaminated sediments is a key element in envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Estuarine sediment toxicity/bioaccumulation tests should be carried out on organisms that are tolerant to variable abiotic conditions, such as pH (Martín-Díaz et al 2008). The commonly used clam, Ruditapes philippinarum, is an infaunal estuarine organism able to adapt to a wide range of salinity and pH values (DelValls and Conradi 2000). Moreover, clams are filter-suspension-feeding bivalves that accumulate metals within their tissues (Shin et al 2002).…”
mentioning
confidence: 99%
“…Estuarine sediment toxicity/bioaccumulation tests should be carried out on organisms that are tolerant to variable abiotic conditions, such as pH (Martín-Díaz et al 2008). The commonly used clam, Ruditapes philippinarum, is an infaunal estuarine organism able to adapt to a wide range of salinity and pH values (DelValls and Conradi 2000). Moreover, clams are filter-suspension-feeding bivalves that accumulate metals within their tissues (Shin et al 2002).…”
mentioning
confidence: 99%
“…A maximum dose Insects 2023, 14, 645 2 of 12 laboratory bioassay was recently proposed for whiteflies as a less costly, more efficient alternative to assessing insecticide efficacy in field populations than multiple spray tests [2]. Ecotoxicological studies have often indicated that predicting field response based on a laboratory bioassay can have many problems [3,4]. Therefore, we investigated whether a laboratory insecticide bioassay for whitefly control precisely and accurately estimates field whitefly response to the insecticide.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of biological responses and chemical data of the sediment helps identify the integrated impact of chemical contamination on organisms. Many authors agree that sediment quality is best determined by integrating the information obtained from measures of chemical concentration and from specific tests to determine sediment toxicity [10,11].…”
Section: Introductionmentioning
confidence: 99%